The financial freedom guarantee. - Robinson, Marco (Morgan James Publishing : Made available through hoopla, 2016)
Are you tired of working for a living? Are you fed up of only JUST being able to pay your bills? Are you sick of thinking about work every single day? Are you going crazy thinking someone will take your Job? Millions are in the same boat as you! Now for the first ever, THE Award Winning 10 step Property Buying System to replace your Salary with Passive Income, Fire Your Boss & Retire Tomorrow is HERE! Never before is having a Job so precarious. There is no such thing as a job for life anymore. People are getting outsourced, paid less, told to work longer hours and are being replaced with Robots and imminently Artificial Intelligence. "The Financial Freedom Guarantee" is for people that really want to start doing what they LOVE to do instead of doing what they have to do to pay the bills. "The Financial Freedom Guarantee" teaches you how to create enough Passive Income from Four Award Winning Property Investment Tools that create enough Positive Cash-flow to replace your Living Expenses. Meaning you never have to rely on a Salary ever again. And thousands of readers are doing it within 90 days! Never before has a body of work been so relevant and timely in a world full of debt and servitude. Even in the last 9 months, although it sounds staggering to believe, Marco has purchased 96 properties, using other people's money & created millions of dollars in profits. . .more importantly he has helped thousands of his students do the same. From the #1 Bestselling Author who WON the People's Choice Best Real Estate Investor for 2015. The Award Winning Retirement Plan that has already helped thousands of people quit their jobs FOREVER!